Proposta de ensino para o tema 'calor' direcionado à mobilização dos estudantes do ensino médio para aprender física - Trevisan, Thaís Lourençato (2021)
The study starts from the premise that the teaching of Physics needs to be restructured in order to allow students to be aware of their knowledge, having control over their actions, which brings them closer to the understanding of metacognition. Furthermore, it presumes that the contextualization of knowledge against everyday situations can act as a mobilizer for students learning Physics. In this sense, it answers the following question: what is the relevance of a teaching proposal based on contextualization and metacognitive reflection, in terms of student engagement and the mobilization of their knowledge? Therefore, it presents a didactic proposal developed for the teaching of Thermal Physics, involving different didactic strategies and situations that comprehend the contextualization and activation of metacognitive thinking. The objective is to evaluate it, seeking to identify its potential and limits. Initially planned for face-to-face application, this didactic proposal had to be adapted due to the pandemic of the New Coronavirus (Covid-19), which imposed a series of changes to the school context in the year 2020. Thus the activities were reorganized into the remote synchronous teaching modality, without, however, losing the main focus: contextualization and metacognitive reflection. After being adapted, the teacher’s support material, produced in the study, was applied remotely synchronously to a group of eighteen students in a second-year high school class at a state school in the countryside of Rio Grande do Sul. The activities were developed by the class’ teacher over ten meetings. Based on this application, a qualitative study was carried out, the results of which involved direct observation in the classroom (video recordings of the meetings), the teacher's record in her logbook and the answers of twelve students to a questionnaire on motivation to learn Physics, applied in the step prior to the development of activities. As a result, it was found that the students have an intrinsic motivation slightly higher than the extrinsic when it comes to learning Physics; the engagement of students in the classes of this discipline was associated with the use of technological resources and the process of contextualizing knowledge through the approximation of the subject to real life situations; and the metacognitive reflections provided at the end of the meetings proved to be a mechanism for monitoring and controlling learning that had repercussions on students' awareness of their own knowledge or, alternatively, the lack thereof. The educational product that accompanies this dissertation is presented as the teacher’s support material and consists of a set of activities organized in meetings <http://educapes.capes.gov.br/handle/capes/599214>.